2016
DOI: 10.1002/jsfa.7592
|View full text |Cite
|
Sign up to set email alerts
|

Detoxification and safety evaluation of aflatoxin B1in peanut oil using alkali refining

Abstract: These results indicate that alkali refining is an effective method for removing AFB1 in peanut oil. The optimum detoxifying conditions of AFB1 in peanut oil with alkali refining could be used to guide the production of oil companies for ensuring food safety. © 2015 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…Due to improper cultivation, process, and storage, some hazardous substances are also detected in EPOs. These substances can be divided into two types: (i) biological hazards and (ii) harmful chemical substances (Ji et al, 2016).…”
Section: Hazardous Substances In Eposmentioning
confidence: 99%
“…Due to improper cultivation, process, and storage, some hazardous substances are also detected in EPOs. These substances can be divided into two types: (i) biological hazards and (ii) harmful chemical substances (Ji et al, 2016).…”
Section: Hazardous Substances In Eposmentioning
confidence: 99%
“…It is estimated that over 5 billion people worldwide are at risk of chronic exposure to AFs in food [4]. Traditional methods of degradation of aflatoxin B1, including physical [8], chemical [9], and microbial approaches [10], suffer from the drawbacks of being time consuming, the loss of nutrients, lowering of quality, increased cost, and formation of toxic residues or derivatives [11,12]. Enzymatic degradation of AFB1 is effective and environmentally friendly, especially in food and feed industries [13].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Wang et al investigated whether CotA laccase from Bacillus subtilis (BsCotA) was capable of detoxifying AFB1 and zearalenone (ZEN) using structurally defined chemicals and complex natural mediators, and the degraded products of AFB1 using the LMS were detoxified [20]. In more recent studies, Guo et al found that recombinant CotA laccase from Bacillus licheniformis transformed AFB1 to AFQ1 and epi-AFQ1, which did not suppress Traditional methods of degradation of aflatoxin B 1 , including physical [8], chemical [9], and microbial approaches [10], suffer from the drawbacks of being time consuming, the loss of nutrients, lowering of quality, increased cost, and formation of toxic residues or derivatives [11,12]. Enzymatic degradation of AFB 1 is effective and environmentally friendly, especially in food and feed industries [13].…”
Section: Introductionmentioning
confidence: 99%
“…1 These aflatoxins exist widely in various grain and animal products. [2][3][4] Among foodstuffs, edible oils such as peanut oil, corn oil, and soybean oil are easily contaminated by various mycotoxins, which could enter the human food chain to potentially impair human growth and increase the incidence of liver cancer. 5,6 Therefore, many countries have established strict regulations on the maximum residue level (MRL) for aflatoxins (B1 + B2 + G1 + G2).…”
Section: Introductionmentioning
confidence: 99%